Effect of Trump tweets on the S&P500 - Tan, Gaddiel T. (Animo Repository, 2022)
This paper aims to look at the effect of Trump tweets to the stock market, specifically the S&P500. Data from 01 January 2007 to 1 June 2017 are used to analyze whether there is a significant difference in the stock market when President Donald J. Trump tweets. A time series analysis of the stock market data is also conducted.